A case-control comparison of direct healthcare-provider medical costs of chronic idiopathic constipation and irritable bowel syndrome with constipation in a community-based cohort. (4th March 2017) - Herrick, Linda M.; Spalding, William M.; Saito, Yuri A.; Moriarty, James; Schleck, Cathy
Abstract: Objective: Patients with constipation account for 3.1 million US physician visits a year, but care costs for patients with irritable bowel syndrome with constipation (IBS-C) or chronic idiopathic constipation (CIC) compared to the general public have received little study. The study aim was to describe healthcare utilization and compare medical costs for patients with IBS-C or CIC vs matched controls from a community-based sample. Methods: A nested case-control sample (IBS-C and CIC cases) and matched controls (1:2) for each case group were selected from Olmsted County, MN, individuals responding to a community-based survey of gastrointestinal symptoms (2008) who received healthcare from a participating Rochester Epidemiology Project (REP) provider. Using REP healthcare utilization data, unadjusted and adjusted standardized costs were compared for the 2- and 10-year periods prior to the survey for 115 IBS-C patients and 230 controls and 365 CIC patients and 730 controls. Two time periods were chosen as these conditions are episodic, but long-term. Results: Outpatient costs for IBS-C ($6, 800) and CIC ($6, 284) patients over a 2-year period prior to the survey were significantly higher than controls ($4, 242 and $5, 254, respectively) after adjusting for co-morbidities, age, and sex. IBS-C outpatient costs ($25, 448) and emergency room costs ($6, 892) were significantly higher than controls ($21, 024 and $3, 962, respectively) for the 10-year period prior. Unadjusted data analyses of cases compared to controls demonstrated significantly higher imaging costs for IBS-C cases and procedure costs for CIC cases over the 10-year period. Limitations: Data were collected from a random community sample primarily receiving care from a limited number of providers in that area. Conclusions: Patients with IBS-C and CIC had significantly higher outpatient costs for the 2-year period compared with controls. IBS-C patients also had higher ER costs than the general population.